Problematika Alih Fungsi Lahan Pertanian di Karanganyar dalam Perspektif Perlindungan Lingkungan - Retna Nurhidayah; Rahayu Subekti; Purwono Sungkowo Raharjo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Rapid population growth in Indonesia, especially in Karanganyar Regency, has contributed to the conversion of agricultural land to non-agricultural land, which has the potential to threaten food security and environmental sustainability. With the main agricultural land protection regulation in Undang-Undang Nomor 41 Tahun 2009 with further regulations in Karanganyar Regency through regional regulations on Karanganyar Regional Peraturan Daerah Karanganyar Nomor 19 Tahun 2019 Perubahan Atas Peraturan Daerah Nomor 1 Tahun 2013, Peraturan Daerah Karanganyar Nomor 6 Tahun 2020 and the basis for the Kesesuaian Kegiatan Pemanfaatan Ruang (KKPR) policy with the Online Single Submission (OSS) system based on the Peraturan Menteri Agraria dan Tata Ruang (ATR) Nomor 13 Tahun 2021. However, in the implementation of these various arrangements there are various problems and challenges. This study aims to analyse the various challenges and problems in the efforts to realize the conversion of agricultural land to non-agricultural land in Karanganyar. This study uses a juridical empirical research method, using a legislative approach and a conceptual approach. The research findings show that there are inconsistencies in regulations, weak supervision and law enforcement, and lack of public awareness and participation.